A graphical user interface (GUI) toolkit for the calculation of three-dimensional (3D) multi-phase biological effective dose (BED) distributions including statistical analyses. Issue 131 (July 2016) - Kauweloa, Kevin I.; Gutierrez, Alonso N.; Stathakis, Sotirios; Papanikolaou, Niko; Mavroidis, Panayiotis
Highlights: A GUI was created to calculate the multi-phase BED distributions. The GUI is effective at determining the BED distributions and the dose statistics of the ROIs for multi-phase treatment plans. Using this GUI has shown the inaccuracies of using the approximate BED calculation method for multi-phase cases. This GUI can be used to optimize multi-phase treatment plans. Abstract: A toolkit has been developed for calculating the 3-dimensional biological effective dose (BED) distributions in multi-phase, external beam radiotherapy treatments such as those applied in liver stereotactic body radiation therapy (SBRT) and in multi-prescription treatments. This toolkit also provides a wide range of statistical results related to dose and BED distributions. MATLAB 2010a, version 7.10 was used to create this GUI toolkit. The input data consist of the dose distribution matrices, organ contour coordinates, and treatment planning parameters from the treatment planning system (TPS). The toolkit has the capability of calculating the multi-phase BED distributions using different formulas (denoted as true and approximate). Following the calculations of the BED distributions, the dose and BED distributions can be viewed in different projections (e.g. coronal, sagittal and transverse). The different elements of this toolkit are presented and the important steps for the execution of its calculations are illustrated. The toolkit is applied on brain, head & neck and prostate cancer patients, who received primary and boost phases in order to demonstrate its capability in calculating BED distributions, as well as measuring the inaccuracy and imprecision of the approximate BED distributions. Finally, the clinical situations in which the use of the present toolkit would have a significant clinical impact are indicated.